Peran Pelatihan dan Pengawasan dalam Meningkatkan Kinerja Karyawan - Ana Septia Rahman; Angga Pratama; Sigit Purnomo (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to examine the role of training and supervision in improving employee performance at PT SJS AEON Delight Indonesia. A quantitative approach with an associative research design was employed. The study involved all employees of PT SJS AEON Delight Indonesia, with a total sample of 72 respondents selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using simple and multiple linear regression, correlation analysis, coefficient of determination, and partial and simultaneous hypothesis testing. The findings indicate that training contributes positively to employee performance by enhancing employees' knowledge, skills, and work capabilities. Supervision also plays a significant role in improving employee discipline, compliance with organizational procedures, and overall work effectiveness. Furthermore, training and supervision complement each other in fostering higher employee performance.